THE ROLE OF ORGANIZATIONAL CULTURE ON IMPROVING EMPLOYEE PERFORMANCE THROUGH WORK DISCIPLINE - Didit Haryadi (Jurnal Mantik, 2022)
The Department of Public Works and Spatial Planning in Pandeglang Regency has several problems that must be resolved, including employee performance that is less than optimal. This study aimed to determine whether organizational culture impacts employee performance through work discipline. This study takes a causal approach and uses a quantitative descriptive methodology. Using a sample of 133 respondents, the Department of Public Works and Spatial Planning of Pandeglang Regency became the place of this research. Responses to the questionnaire were rated on a scale of 1 to 10. SmartPLS Software Version 3.29 was used to evaluate the information. Based on the results of this study, 1). Employee performance is influenced by organizational culture. 2). Work discipline is strongly influenced by corporate culture. 3). Employee performance is influenced by work discipline. Work discipline can partially bridge the relationship between organizational culture and performance. It is possible to improve employee performance by directly enhancing the values of the organizational culture or by enforcing work discipline.